(untitled) (Research, Society and Development, 2022)
This essay aims to present and explain a concept of Education 5.0, the result of a systematization based on studies, research and reflections. Education 5.0 is an evolution of educational approaches 1.0, 2.0, 3.0 and 4.0, which are linked to historical events of global impact. This is a broad educational approach that integrates Digital Technologies and Artificial Intelligence in contexts where the student is active, creative, critical and reflective and their interests, difficulties and potential are considered, aiming at the development of skills to live in the 21st century; a century marked by numerous challenges, which intensified with the Covid-19 pandemic. However, Education 1.0 is still prevalent in many schools in Brazil and around the world, as the educational process boils down to teaching and testing. Therefore, it is pointed out the need to (re)think the teaching and learning processes, starting with the development of research and training for teachers on the Education 5.0 theme.